Electronic Structure and Electromagnetic Properties for 2D Electromagnetic Functional Materials in Gigahertz Frequency. Issue 4 (11th February 2019) - Cao, Mao‐Sheng; Shu, Jin‐Cheng; Wang, Xi‐Xi; Wang, Xin; Zhang, Min; Yang, Hui‐Jing; Fang, Xiao‐Yong; Yuan, Jie
Abstract: Two‐dimensional (2D) materials exhibit massive potential for research and development in the scientific world due to the unique electrical, optical, thermal, and mechanical properties. Particularly, they have received intensive attentions in the microwave absorption (MA) and electromagnetic interference (EMI) shielding. Herein, the structure and electronic state of 2D materials are examined systematically, and the origination of electromagnetic (EM) response is shown, including electron transport, dipole relaxation, magnetic resonance, and eddy current. Furthermore, the latest research progress of 2D materials in EM field is introduced, and the application prospect and limitation are highlighted. Abstract : Two‐dimensional materials exhibit massive potential for research and development in the scientific world. Here, the structure and electronic state of 2D materials are explored systematically, and the origination of electromagnetic response is shown. Furthermore, the latest research progress of 2D materials in EM field is introduced, and the application prospect and limitation are highlighted.